Co‐production in climate change research: reviewing different perspectives. (20th July 2017) - Bremer, Scott; Meisch, Simon
Abstract : Notions of 'co‐production' are growing in popularity in social science and humanities research on climate change, although there is some ambiguity about the meanings of the term and how it is being used. It is time to critically and reflexively take stock of this expanding area of scholarship. A comprehensive review of over 130 scientific publications first mapped the scholars using co‐production, relative to characteristics like their discipline, nationality, and research themes. Second, it looked at how this diversity of scientific perspectives has opened up a multiplicity of meanings of co‐production. While most discussions of co‐production stop at a basic distinction between descriptive and normative uses of the term, this review unpacked eight conceptual lenses on co‐production, each discernible by its particular emphases, academic traditions, logic, and criteria of success. There are two important implications of this work. On one hand, it urges self‐reflexive transparency when using co‐production concepts. The multiple meanings attached to co‐production add richness to the concept and open it up to different uses. However, it is important that scholars clearly communicate how they use the term and are mindful of what they 'buy into' by using the concept in certain ways. On the other hand, there are tensions between the different perspectives as well as opportunities for combining them into a compound concept of co‐production. In this way, co‐production is reconceptualized as a prism, where each aspect allows different but complimentary insights on the relationship between science, society, and nature. WIREs Clim Change 2017, 8:e482. doi: 10.1002/wcc.482 This article is categorized under: Social Status of Climate Change Knowledge > Knowledge and Practice Abstract : This paper reconceptualizes co‐production as a prism, which comprises eight different aspects or ways of using co‐production uncovered in the social science and humanities research on climate change, two mainly descriptive and two mainly normative. Each aspect reveals a different dimension of co‐production, steered by its particular emphasis, academic tradition, logic, and criteria of success.